CONDUCTIVITY OF SOLID FLUORIDE-CONDUCTING PHASES BaxPb0.86-xSn1.14F4 - Nahornyi, Anton; Voloshanovska, Yulia; Omelchuk, Anatolii (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2022)
This work presents the results of research of complex solid fluoride ion conducting phases based on lead and tin fluorides. Structure and conductive properties of solid solutions based on PbSnF4 were investigated. Series of samples were synthesized with replacement of lead cations with barium cations in structure of Pb0.86Sn1.14F4 in the concentration range of 0 ≤x ≤0.86. The barium cation has a larger radius and does not have a stereoactive lone pair of electrons, which can have a significant contribution to the conductivity of the synthesized phases and the characteristics of fluoride ion transportation in them. It was established that with partial or complete replacement of lead cations with barium cations in the fluoride ion conducting phases in Pb0.86Sn1.14F4 solid solutions of BaxPb0.86‑xSn1.14F4 , where x takes the values 0 ≤x ≤0.86 are formed. The symmetry of the crystal lattice of the synthesized phases in the concentration range of 0 ≤x ≤0.43 corresponds to the structural type of β-PbSnF4 (space group P4/ nmm). Farther increase in the content of barium fluoride cause their crystal lattice to rearrange and approach the structural type of BaSnF4 with preservation of the space group symmetry. The conductive properties of the synthesized phases were investigated. We register increase in conductivity of samples bound to increase of barium cation content in the range of 0 ≤x ≤0.43. After reaching peak in conductivity of samples it gradually lowers with increase of barium cation content in the range of 0.43 ≤x ≤0.86. The fluoride ion conducting phase Pb0.43Ba0.43Sn1.14F4, isostructural to β-PbSnF4, in comparison with the currently known fluoride-conducting phases has have the highest electrical conductivity in a wide temperature range. Its conductivity is almost two orders of magnitude higher than that of β-PbSnF4 and is 0.12 S/cm at 373 K. With 19FNMR method, it was determined that electrical conductivity is mainly provided by internodal fluorine anions, which are localized between layers of barium and stanium cations. The transfer numbers for fluorine anions in the synthesized phases correspond to the theoretical ones.